Pengaruh Mobile Legends terhadap Prestasi Akademik Mahasiswa PGSD - Fauziah, Zumrotul; Saputri, Ayunda Nadea; Firani, Arinda Cahya; Rahmadani, Yola; Fristayana, Lollita (Elementary Education Journal, 2022)
Background: This study aims to test whether there is an influence between the Mobile Legend game on the academic achievement of UMS PGSD students. Method: The method used in this study was descriptive quantative. Sampling using simple random sampling technique. Samples were taken from class D semester IV PGSD UMS as many as 20 students. This study uses one independent variable, namely the Mobile Legends game (X) and one dependent variable, namely student academic achievement (Y). The data used in this study were a questionnaire with 20 respondents and the Semester Grade Point Average (IPS) III. This research method uses ex post facto with a quantitative approach. The data analysis used was a simple linear regression analysis technique, all calculations used SPSS version 25. Result: The results of this study revealed a significance value (Sign.) of 0.896 which means greater than 0.05. In addition, the independent variable (Mobile Legends game) obtained t count = - 0.132 < 2.10092 = t table. So it can be concluded that H0 is accepted and Ha is rejected, which means there is no significant effect between the Mobile Legends game (X) on student academic achievement (Y).  Implication: The implications of this study are: First, the public in Indonesia should enrich the teachers' knowledge and insight related to support another non academic achievment. Second, the government, supported by researchers, has to design an excellent assessment system to solve time limitations. Novelty: The present study revealed the implementation of academic achievment.